An Empirical Study on the Influence of the Basic Medical Insurance for Urban and Rural Residents on Family Financial Asset Allocation - Li, Shenglin; Yang, Yifei (Frontiers in Public Health, 2021)
Based on the China Household Finance Survey micro data of 2013, 2015, and 2017, this study empirically examined whether participation in the Basic Medical Insurance for Urban and Rural Residents impacted families’ allocation to risk assets and risk-free assets using the Heckman two-step method. We tested the robustness of the benchmark model and the mediating effect model with different definitions of risk assets and risk-free assets. The results showed that participation in the Basic Medical Insurance for Urban and Rural Residents can promote families’ reasonable choice between risk assets and risk-free assets to a certain extent. The analysis of the mechanism showed that this also increases families’ risk perception—turning their risk attitude more cautious and their investment attitude more rational. For the originally risk-seeking families, the risk asset investments are squeezed out; however, for the originally risk-adverse families, the risk-free asset investments are squeezed out. To further consolidate the social security attributes of the Basic Medical Insurance for Urban and Rural Residents, behind its high coverage, we should also pay attention to its influence on the investment preferences of families with different social and economic statuses, thereby giving full play to its role in promoting the development of China’s financial market.